RIGHT OF EXPRESSION IN PERGUB D.I YOGYAKARTA NUMBER 1 YEAR 2021PERSPECTIVE SIYASAH DUSTURIYYAH - Siagian, Siti Saadah (MIZAN: JOURNAL OF ISLAMIC LAW, 2022)
The Government of the Special Region of Yogyakarta issues and stipulates the Governor's Regulation (Pergub) DIY Number 1 of 2021 concerning implementing Public Expression of Opinions in Open Space. Article 5 of the Pergub reads that "Public Opinion is carried out in an open space for the public in the Region by the provisions of the legislation, except in the State Palace Area, the Great Building, the Kraton of the Ngayogyakarta Hadiningrat Sultanate, the Kraton of the Duchy of Pakualaman, Kotagede; and Malioboro a polemic amid society because it is considered to violate the fundamental rights of citizens, especially in the human rights scheme in Islam which is regulated in the Siyasah Dusturiyyah. The purpose of this research is to explain the perspective of Siyasah Dusturiyyah and explain the concrete solution to the problem. This type of research is library research with a juridical-normative approach. This study found that the Regulation of the Governor of the Special Region of Yogyakarta Number 1 of 2021 juridically does not contradict the above laws and regulations. Still, philosophically the norms in the human rights scheme in Islam adhere to several principles, namely the principle of equality, the principle of Freedom, and the principle of respect for fellow human beings who experience anomalies and are injured, where policymakers should be able to guarantee, maintain and protect the fundamental rights of citizens, in this case, the right to express opinions by not castrating the rights of some people and then for the sake of some other people's rights. At this point, the responsibility holders must jointly be able to accommodate all requests so they can be carried out together correctly.